From fear to fortitude: academic adjustment during COVID-19 among South African undergraduates - Tau, Matumelo Maria; Mapaling, Curwyn; Tsabedze, Wandile Fundo (Frontiers in Education, 2024)
IntroductionThe outbreak of COVID-19 introduced unprecedented uncertainty worldwide, with South Africa being no exception. There is a paucity of information on the impacts of academic adjustment and fear of COVID-19 among undergraduate students in a new university environment. This study aimed to examine the relationship between academic adjustment and fear of COVID-19 among undergraduate students enrolled at a South African University.MethodsA cross-sectional correlational research design was employed, utilizing web-based questionnaires that combined the Academic Adjustment Scale and the Fear of COVID-19 Scale. The theoretical framework used was the self-transcendence theory, supported by theoretical perspectives on adjustment and differential susceptibility theories. A total of 501 participants were selected through simple random sampling. Data were analyzed using descriptive and inferential statistics, including simple linear regression correlation analysis and multivariate analysis of variance.ResultsFear of COVID-19 showed a significant positive correlation with academic adjustment (r = 0.17, p < 0.001). Additionally, fear of COVID-19 was positively correlated with dimensions of academic adjustments, specifically academic achievement (r = 0.19, p < 0.001) and academic motivation (r = 0.20, p < 0.001).DiscussionThe study concluded that there was a significant positive correlation between fear of COVID-19 and academic adjustment. Therefore, it is crucial to implement interventions aimed at continuously enhancing students' academic adjustment as a seamless process.